Handbook of Sustainability and Social Science Research (World Sustainability Series,, 2018)
In this handbook social science researchers who focus on sustainability present and discuss their findings, including empirical work, case studies, teaching and learning innovations, and applied projects. As such, the book offers a basis for the dissemination of information, ideas and experiences acquired in the execution of research projects, especially initiatives which have influenced behavior, decision-making, or policy. Furthermore, it introduces methodological approaches and projects which aim to offer a better understanding of sustainability across society and economic sectors. This multidisciplinary overview presents the work of researchers from across the spectrum of the social sciences. It stimulates innovative thinking on how social sciences influence sustainable development and vice-versa.